Five S factory makeover - Bollinger, Steven R; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2005)
Starting with an explanation of why a company should keep its manufacturing areas clean, this program shows you an actual Five S training event at two different manufacturing companies. Five S stands for Sort out, Set in order, Shine, Standardize, and Sustain
Code no : DV05PUB12
Title from title screen
Executive producer, Mark Tomlinson ; camera, Tom Gereneer ; editor, David Rembiesa
Keywords: Factory management; Production management